Assessing limb dominance and interlimb asymmetries over multiple angles during change of direction speed tests in basketball players - Gonzalo-Skok, O.; Dos'Santos, T.; Bishop, C. (The Journal of Strength and Conditioning Research, 2023)
The aims of this study were to establish whether directional dominance is displayed during change of direction (COD) tasks across various angles, to determine the angle-variation data for the asymmetry magnitude and direction, and to analyze the relationships in COD performance (completion time and COD deficit) across tasks. Twenty-four young (U-16 to U-20), highly trained male basketball players performed a 10-m linear sprint test and four 10-m COD tests (45°, 90°, 135°, and 180°) in left and right directions. Change of direction performance was determined via total times and COD deficit, and asymmetry comparisons were made between faster and slower directions and dominant leg (DL) (i.e., first step leg in lay-up) and nondominant leg (NDL). No significant differences (p > 0.05) were found between DL and NDL for any task excluding 45° COD (p < 0.05, effect size [ES] = 0.44-0.78), but significant differences were established between faster and slower sides for all angles (p < 0.05, ES = 0.70-1.28). Levels of the agreement in directional dominance during COD tasks were generally poor to slight (k = -0.14 to 0.14), excluding a fair agreement between COD45 and COD90 (k = 0.34). Correlations between COD total times and COD deficits between angles were moderate to very large (r = 0.32 to 0.81) and moderate to large (r = -0.30 to 0.55), respectively. Players displayed superior COD performance in a particular direction across various angles. This directional dominance is not necessarily consistent between angles, thus highlighting the angle-dependent nature of COD performance. Consequently, practitioners should investigate multiple angles and directions to create a COD angle profile for their athletes.